Oleksandr Dovzhenko and the Soviet Secret Police - Rosliak, Roman (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article reviews the specifics of the surveillance process of the Ukrainian film director Oleksandr Dovzhenko organized by the Soviet secret police. The main focus is on agents’ reports about the director’s work on the films Earth, Ivan, Shchors, and the screenplay for Ukraine in Flames. The article reveals that Dovzhenko was under permanent secret police surveillance, starting from the end of the 1920s until the end of his life in 1956. This surveillance was well organized; it was large-scale and complex in its nature and covered not only his professional but his private life as well. The purpose of the surveillance was to collect and analyze compromising, i.e., anti-Soviet information against the film director and, if necessary, to open a criminal case against him, and make an arrest.